2016
DOI: 10.1080/10837450.2016.1265554
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of solubility, dissolution and stability profile of artemether solid dispersions and self emulsified solid dispersions by solvent evaporation method

Abstract: The purpose of this study was to investigate changes in the water solubility of artemether; a poorly soluble drug used for the treatment of malaria. Different solid dispersions (SDs) of artemether were prepared using artemether and polyethylene glycol 6000 at ratio 12:88 (Group 1), self-emulsified solid dispersions (SESDs) containing artemether, polyethylene glycol 6000, cremophor-A-25, olive oil, hydroxypropylmethylcellulose and transcutol in the ratio 12:75:5:4:2:2, respectively (Group 2). SESDs were also pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Various approaches have been employed to try and improve the solubility and thus anti-malarial activity of both of the components in Coartem® including nanostructured lipid carriers, self-emulsified solid dispersions, solid lipid microparticles and nanoemulsions ( Agbo et al, 2016 ; Laxmi et al, 2015 ; Parashar et al, 2016 ; Tayyab Ansari et al, 2016 ). Recently, it was demonstrated that lumefantrine amorphous solid dispersions improved its oral absorption relative to the crystalline reference ( Jain et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Various approaches have been employed to try and improve the solubility and thus anti-malarial activity of both of the components in Coartem® including nanostructured lipid carriers, self-emulsified solid dispersions, solid lipid microparticles and nanoemulsions ( Agbo et al, 2016 ; Laxmi et al, 2015 ; Parashar et al, 2016 ; Tayyab Ansari et al, 2016 ). Recently, it was demonstrated that lumefantrine amorphous solid dispersions improved its oral absorption relative to the crystalline reference ( Jain et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Amorphous solid dispersions present a promising strategy for improving the bioavailability of poorly soluble drugs [ 30 , 31 , 32 ]. Solid dispersions can be prepared by thermal methods (e.g., melting and hot-melt extrusion (HME)) [ 33 , 34 , 35 ], solvent evaporation [ 36 , 37 ], and supercritical fluid technology [ 38 , 39 , 40 ]. Binary solid dispersions of highly lipophilic drugs such as atovaquone and polymeric carriers are limited in their drug loading capacity and therefore their feasibility due to dissolution rate limitations [ 41 ].…”
Section: Introductionmentioning
confidence: 99%
“…Conversion of crystalline nateglinide into amorphous state also might be another reason for enhancement of solubility. 23…”
Section: Preparation Of Samplementioning
confidence: 99%